Cost of Production for Fresh Market Grapefruit Grown in Indian River, 2017/18 - Ariel Singerman (EDIS)
This 4-page fact sheet written by Ariel Singerman and published by the UF/IFAS Food and Resource Economics Department presents the cost of production per acre for growing fresh grapefruit in the Indian River region during 2017/18. The methodology chosen to collect the data consisted of surveying growers directly to closely reflect growers' costs in the era of citrus greening. Typical users of the estimates in the fact sheet include growers and consultants, who use them as a benchmark; property appraisers, who use them to compute the taxes for property owners; and researchers, who use the estimates to evaluate the economic feasibility of potential new technologies. http://edis.ifas.ufl.edu/fe1066